2020
DOI: 10.21203/rs.3.rs-62930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significance of serum branched-chain amino acid to tyrosine ratio measurement in athletes with high skeletal muscle mass

Abstract: Background Few nutritional markers reflect the hypermetabolic state of athletes with high levels of skeletal muscle. Although branched-chain amino acids (BCAA) play crucial roles in protein metabolism in skeletal muscle, the relationship between circulating BCAA concentration and skeletal muscle mass has not been fully understood. The aim of this study is to evaluate the association between skeletal muscle mass and serum BCAA to tyrosine ratio (BTR), a convenient indicator of circulating BCAA, in young Japane… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, ongoing efforts are made to determine the prognostic value of plasma concentration ratios as an easily measurable proxy for metabolic flux markers. Special attention is given to the plasma amino acid concentration ratio between the BCAA and the aromatic amino acids [17][18][19][20].…”
Section: New Flux Measurement Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ongoing efforts are made to determine the prognostic value of plasma concentration ratios as an easily measurable proxy for metabolic flux markers. Special attention is given to the plasma amino acid concentration ratio between the BCAA and the aromatic amino acids [17][18][19][20].…”
Section: New Flux Measurement Approachmentioning
confidence: 99%
“…For instance, the hypothesis was tested that athletes with a large skeletal muscle mass have plasma amino acid imbalances, assessed by the serum BCAA to tyrosine ratio [20]. The study showed a decrease in serum BCAA/tyrosine ratio with increased skeletal muscle mass.…”
Section: New Flux Measurement Approachmentioning
confidence: 99%